Competitive Host-guest Electrochemical Detection of Ivermectin Drug Using a β-cyclodextrin/Graphene-based Electrode - Silva, Martin K. L. [UNESP]; Simões, Rafael P. [UNESP]; Leão, Alcides L. [UNESP]; Lapa, Rainer M. L.; Rascón, Jesús; Cesarino, Ivana [UNESP] (Wiley, 2022)
The present study describes the novel development and application of an ivermectin (IVM) sensing electrochemical platform based on reduced graphene oxide (rGO) and the macrocyclic host β-cyclodextrin (β-CD) molecule. The sensing method was based in the host-guest characteristics of β-CD and competitive interaction between the target analyte and the methylene blue (MB) redox probe. Differential pulse voltammetry (DPV) was employed for the detection of IVM and a linear response between 0.5 and 40.0 μmol L−1 with a limit of detection of 0.25 μmol L−1 was obtained using the glassy carbon (GC)/rGO/β-CD electrode. The sensing platform was successfully applied for the detection of IVM in tap water samples, which may expand the applications of β-CD towards the analysis of other chemical species.
Keywords: Electrochemical sensors; Graphene; Host-guest interaction; Ivermectin; β-Cyclodextrin